Стратегії реалізації авторитарного домінування у комунікації сіблінгів - Звєрєва, Ольга Геннадіївна; Zvereva, O. G. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проаналізовано стратегічну організацію асиметричної комунікації сіблінгів залежно від соціального статусу. Здійснено спробу окреслити синтаксичні, семантичні та прагматичні особливості комунікативних стратегій, які вживають сіблінги в ситуації авторитарного домінування. Авторитарність трактують як характеристику комунікативного процесу, спрямовану на здійснення психологічного тиску на адресата з порушенням принципу ввічливості та максим комунікації. До головних стратегій авторитарного домінування належить експліцитне вимагання виконання вимог адресанта, інтенсифікація авторитетності мовця та пригортання уваги до обраних домінуючим сіблінгом тем комунікації. The article analyzes strategic organization of asymmetrical communication between siblings, with inequality based on the relevant social status. The article presents an attempt to describe syntactic, semantic and pragmatic peculiarities of communication strategies used by siblings in the situation of authoritative dominance. The siblings’ discourse is characterized by relations of dominance/submission which in the adulthood are based on the social status, psychological characteristics, including the leadership qualities, and on the established intrafamily relations and typical family roles. Authoritarianism as a characteristic of the communication process, aimed at exercising psychological pressure with violation of politeness principles and communication maxims, in siblings’ interaction is enabled by a significant difference in the relative statuses between siblings which is achieved by combining several sources of dominance. It was revealed that the principal strategies of authoritative dominance are the explicit demand of performing the speaker’s instructions, intensification of the speaker’s authority and drawing attention to the communication themes determined by the domineering sibling.
Strategies of Authoritative Dominance in Siblings’ Communication
Keywords: комунікація сіблінгів; siblings’ communication; домінування; dominance; комунікативна стратегія; communication strategy